Inokulasi Fungi Mikoriza Arbuskula (FMA) Indigenus pada Bibit Jahe untuk Pengendalian Penyakit Layu Ralstonia solanacearum ras 4) - Suharti, Netty; Habazar, Trimurti; Nasir, Nasril; Dachryanus, Dachryanus; Jamsari, Jamsari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Bacterial wilt disease caused by Ralstonia solanacearum race 4 is one of factors inhibiting ginger production. The study on ArbuscularMychorrizae Fungus (AMF) in greenhouse was found could reduce of bacteria wilt disease. Experiment design of research was randomizedblock design using 8 isolates. The results showed that inoculation of Arbuscular Mychorrhizae Fungus isolated from healthy gingerrhizosphere as biological diseases control agents could reduces disease severity. Four isolate could reduced disease severity up to 100% andsupport plant growth and production. As the result the seedling formation increased by 50–150%, plant height 36.92–87.56%, the numberof leaf 61.94–162.22% and ginger yield 190.62–400% respectively, compared to the control.